ANALISIS SWOT : KEBERLANJUTAN PROGRAM KETARUNAAN SEBAGAI PILAR PENDIDIKAN KARAKTER DI SMK NEGERI 1 KONGBENG - Indah Ratna Purwanti; Bambang Setiono; Hediati Mahardika; Yustina Situmorang; Anggy Hanggara; Nurlaili; Usfandi Haryaka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the sustainability of the cadetship program as a pillar of character education at SMK Negeri 1 Kongbeng through a SWOT approach. The study employed a descriptive qualitative method, with research subjects consisting of the principal, vice principal for student affairs, cadetship supervisors, teachers, and students. Data were collected through interviews and documentation, then analyzed by identifying internal and external factors affecting the sustainability of the cadetship program. The findings showed that, based on the IFAS Matrix, the cadetship program obtained a score of 3.42, indicating that its internal condition was in a strong category. The main strengths of the program lie in its integration with school culture, structured activities, support for the development of discipline, responsibility, and leadership, as well as spiritual habituation. Based on the EFAS Matrix, the program obtained a score of 3.60, indicating that external opportunities were more dominant than threats. Supportive character education policies, community expectations, cooperation with parents, and labor market demands were identified as the main opportunities for the program’s sustainability. The program’s position in Quadrant I, with coordinates of 0.66 and 0.78, indicates that the appropriate strategy is the SO strategy, namely utilizing strengths to seize opportunities. Thus, the cadetship program has good prospects to be maintained and developed sustainably as a pillar of character education at SMK Negeri 1 Kongbeng.